2013
DOI: 10.1128/mbio.00524-13
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus Nonstructural Proteins 3, 4, and 6 Induce Double-Membrane Vesicles

Abstract: Coronaviruses (CoV), like other positive-stranded RNA viruses, redirect and rearrange host cell membranes for use as part of the viral genome replication and transcription machinery. Specifically, coronaviruses induce the formation of double-membrane vesicles in infected cells. Although these double-membrane vesicles have been well characterized, the mechanism behind their formation remains unclear, including which viral proteins are responsible. Here, we use transfection of plasmid constructs encoding full-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
523
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 445 publications
(577 citation statements)
references
References 60 publications
21
523
3
2
Order By: Relevance
“…Furthermore, RdRp or nascent viral RNA has not been detected inside DMVs, and ultrastructural analysis could not confirm any connection between the DMV interior and the cytoplasm (38), raising questions about the import and export of ribonucleotide precursors and produced RNAs exported from RNA synthesis areas (44). The coexpression of the SARS-CoV transmembrane nonstructural proteins nsp3, nsp4, and nsp6 resulted in the formation of CMs and DMVs (45), suggesting a function in the biogenesis of the membranous replicative structures, and also in the anchoring of the RTC (4648). …”
Section: Role Of Double-membrane Vesiclesmentioning
confidence: 99%
“…Furthermore, RdRp or nascent viral RNA has not been detected inside DMVs, and ultrastructural analysis could not confirm any connection between the DMV interior and the cytoplasm (38), raising questions about the import and export of ribonucleotide precursors and produced RNAs exported from RNA synthesis areas (44). The coexpression of the SARS-CoV transmembrane nonstructural proteins nsp3, nsp4, and nsp6 resulted in the formation of CMs and DMVs (45), suggesting a function in the biogenesis of the membranous replicative structures, and also in the anchoring of the RTC (4648). …”
Section: Role Of Double-membrane Vesiclesmentioning
confidence: 99%
“…Coronaviruses form a double-membrane organelle (DMO) derived from the endoplasmic reticulum (ER) that contains viral RNA and replicase proteins (Deming et al, 2007;Hagemeijer et al, 2010;Oostra et al, 2007;Shi et al, 1999;van der Meer et al, 1999). In the DMO, two lipid bilayers are held at a constant distance of about 20 nm (Angelini et al, 2013). Electron microscopy and tomography studies have revealed that the replicative organelles of coronaviruses and the related arteriviruses are drawn from a repertoire of paired-membranes, including open-ended spherules, closed double-membrane vesicles, and both planar and convoluted paired membranes (Knoops et al, 2008(Knoops et al, , 2012Maier et al, 2013).…”
Section: Origin Of Dmo Membranesmentioning
confidence: 99%
“…One randomly oriented ultrathin section per cell was examined in order to compare the sizes and numbers of intracellular organelles virions, as described previously (17). …”
Section: Resultsmentioning
confidence: 99%
“…The conserved gene cluster from the nsp3 gene to the nsp6 gene contains all the factors necessary for DMV formation: nsp3, nsp4, and nsp6 are needed to form DMV clusters (17) after essential processing by proteinases located in nsp3 (18) and nsp5 (19). Electron microscopy suggests that nsp3 induces membrane proliferation (17).…”
Section: Introductionmentioning
confidence: 99%